Availability and accessibility to primary health care for the rural area population in Pakistan - Abbas, Muhammad Salman (2025)
Healthcare provision in rural areas of Pakistan remained a critical concern, especially in terms of the availability and accessibility of services. Despite national and international efforts to improve healthcare delivery, rural populations faced disparities due to inadequate infrastructure, workforce shortages, and socioeconomic barriers. This study investigated these issues, focusing on South Punjab, to offer insights into the determinants influencing healthcare access and the effectiveness of government policies. The objectives of this research were to 1) identify the determinants of healthcare availability and accessibility in rural Pakistan; 2) analyze the effectiveness of government policies aimed at improving rural healthcare access; 3) examine the challenges in implementing these policies; and 4) assess the broader impact of healthcare accessibility on education, employment, and social development in rural communities. The study employed a qualitative research design grounded in interpretivism, using thematic analysis to explore the subjective experiences of 15 doctors working in primary healthcare centers as well as one Deputy Commissioner, two community leaders and two Chief Executive Officers across South Punjab. Data was collected through semi-structured interviews, allowing for an in-depth examination of the factors influencing healthcare access. The thematic analysis revealed several key determinants impacting healthcare access, including inadequate infrastructure, workforce shortages, and socioeconomic barriers. Government policies have improved rural healthcare access; however, urban-centric planning, cultural barriers, and systemic inefficiencies continue to hinder progress, leaving significant gaps in rural development. This study contributed to the application of Modernization Theory to explore healthcare access in rural Pakistan. The theory suggested that economic growth and institutional reforms should improve public services like healthcare. In rural areas such as South Punjab, this framework examined how infrastructure, trained professionals, and policy can address healthcare gaps. The study finds that modernization benefits have been uneven, with significant rural-urban disparities. Interviews highlighted systemic issues and policy gaps. Future research could focus on decentralized governance and community-driven initiatives to bridge these healthcare access gaps.